Patients' Perceptions: A Group Differences Study Twelve Months Before and Twelve Months During a Worldwide Pandemic - Nancy Valla (Patient Experience Journal)
Objective: The COVID-19 pandemic subjected healthcare systems' to decreasing operational margins, enhanced regulatory scrutiny, and challenges related to patients' expectations. Until now, there was a lack of empirical evidence studying patients' perceptions prior to versus deep immersion into the pandemic. Methods: This quantitative non-experimental ex post facto causal-comparative study examined if and to what extent there were significant differences in patients' perceptions of the nurses' communications, doctors' communications, overall hospital rating, and willingness to recommend before versus during the COVID-19 pandemic for HCAHPS participating hospitals in California. The final sample size was 292 facilities grouped by two identically matched hospital entity composition for this within-subject group differences analysis. Results: The Wilcoxon Signed-Rank Test revealed statistically significant differences existed between the pre-COVID-19 group and the deeply immersed group on all four research questions: RQ1 Z = 8.66, p < .001; RQ2 Z = 10.089, p < .001; RQ3 Z = 8.44, p < .001; RQ4 Z = 8.81, p < .001. Rejection of the null hypothesis was warranted for all RQs. Conclusions: The importance of this research was applicable to the future of patient safety and quality of care for stakeholders at all levels, patients, family members, healthcare providers, administrators, payer organizations, and regulatory bodies. Whether a payer or health care entity, professionals who utilize HCAHPS results can benefit from this study. It may be time to invest in a recalibration of the HCAHPS associated financial incentives and penalties.